Transcriptome of the SigB overexpression strain of cyanobacterium Synechocystis sp. PCC6803 - Saleem, Tayyab (My University, 2024)
Photoautotrophic cyanobacteria have a great biotechnological potential for bioproduction of commercial metabolites, but robust host strains are needed for practical applications. We have tested if overexpression of a particular transcriptional regulator, sigma (σ) factor SigB, could improve the performance of model cyanobacterium Synechocystis sp. PCC6803 (Synechocystis) as a host organism. SigB regulates many stress-responsive genes, especially in high temperature or oxidative stress. Transcriptome and the σ factor content of the RNA polymerase (RNAP) holoenzyme were analyzed in the SigB overexpression (SigB-oe) strain in standard growth conditions. RT-qPCR analysis indicated four-fold overexpression of sigB in SigB-oe. For comparing the transcriptomes of SigB-oe and control strains, cultures were grown in standard conditions (photosynthetic photon flux density 40 μmol m-2s-1, 32 oC, ambient air), and total RNA was isolated using the hot phenol method and sent for commercial sequencing. Then, the reads were mapped to Synechocystis genome with Bowtie2, counted with HTSeq, and differential expression was analyzed with DESeq2. The transcriptomes of SigB-oe and the control strain were found to be highly similar. To compare the σ factor content of the RNAP holoenzymes, strains containing His-tags in the γ subunit of the RNAP were utilized. The cells were grown in standard conditions, RNAP complexes were pulled down using cobalt-coated magnetic beads, and Western blotting was performed. Similar low SigB content and similar SigA, SigC and SigD contents were measured in the RNAP holoenzymes of both strains, which explains their resembling transcriptomes.
Keywords: cyanobacteria, RNA polymerase holoenzyme, Synechocystis, SigB sigma factor, transcription